NOVA KONCEPCIJA NASTAVE FIZIČKOG VASPITANJA - UVOĐENJE TEHNOLOGIJE MONITORISANJA SRČANE FREKVENCE U CILJU VEČE MOTIVACIJE, EDUKACIJE, KVALITETNE PRIPREME I SELEKCIJE UČENIKA ZA SPORT - Franja Fratrić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Introducing heart rate monitoring using modern pulsemeters in teaching of physical education, extracurricular, sport and other activities would give utterly new aproach in methodics of physical education, pedagogy itself and the attitude of pedagogues in schools concerning teaching of physical education. The purpose of this change is reaching higher health levels of school population. By introducing pulsemetry into schools we will get following benefitions: - Motivation of pupils for exercising and healthy living - Education of pupils. Teaching schoolchildren to listen to their bodies - Helping them to understand characteristics and working of cardiovascular system and integral functioning of organism in various conditions. - Helping teachers to plan training and increase achievements amongst shoolchildren - Enabling the connection of physical education to other subjects: Biology Mathematics Physics Informatics and computer science - Teaching children to analize informations and to show them in different ways - developing creativity and integral way of thinking - Familiarize schoolchildren with high technology